Semi-organic Rice Farming as a Transition Period to Organic Rice Farming - D. Yadi Heryadi; Betty Rofatin; Zulfikar Noormansyah (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2021)
Organic rice farming aims to achieve sustainable agriculture. It considers social, economic and environmental aspects. However, in practice, farmers experience various technical and economic constraints upon converting non-organic agriculture practice to organic rice farming. The alternative method is to implement semi-organic farming as a transitional period. The purpose of this study is to review technical / production and economic aspects of non-organic, semi-organic, and organic farming. It is conducted to determine whether semi-organic farming could be utilized as a transition period to organic rice farming. The study used a survey method on 75 farmers working in non-organic, semi organic, and organic farm in Priangan Timur, West Java Province, Indonesia. Article’s result exhibited that, in terms of technical cultivation / production, the majority of semi-organic farmers had carried out the stages of organic cultivation. It generated higher productivity compared to non-organic farming. However, productivity remained below organic farming. In terms of economical aspect, income per hectare and R / C value are higher than non-organic farming. However, it is below organic farming. Semi-organic farming could be used as a transition to organic farming.